Affect, infrastructure, and vulnerability: Making and breaking Japanese eldercare (Medicine Anthropology Theory, 2016)
Care work requires a vulnerability and ethical responsiveness towards the cared-for, including an openness to ebbs and flows of affective intensity. For care workers, affective vulnerability is not only a precondition for good care but can also precipitate exhaustion, neglect, and even violence under precarious political and economic conditions. I argue that the concept of vulnerability allows us to trouble the distinction between the supposed oppositional forces of care and violence, allowing us to imagine other possible ways of being in the world with others. Drawing on ten months of fieldwork in Kyoto, Japan, I describe how care workers constitute a human infrastructure whose vulnerability facilitates flows of compassion and cruelty, erotic intensity and heavy fatigue. Care workers’ narratives reveal a process of striving to embody vulnerability and sustain moral selfhood without breaking down.